Size-dependent distribution and inhalation cancer risk of particle-bound polycyclic aromatic hydrocarbons at a typical e-waste recycling and an urban site - Luo, Pei; Bao, Lian-Jun; Li, Shao-Meng; Zeng, Eddy Y. (ENVIRONMENTAL POLLUTION, 2015)
Atmospheric particle size distribution of polycyclic aromatic hydrocarbons (PAHs) in a typical e-waste recycling zone and an urban site (Guangzhou) in southern China featured a unimodal peak in 0.56 -1.8 mu m for 4-6 ring PAHs but no obvious peak for 2-3 ring PAHs at both sites. The atmospheric deposition fluxes of PAHs were estimated at 5.4 +/- 2.3 mu g m(-2) d(-1) in the e-waste recycling zone and 3.1 +/- 0.6 mu g m(-2) d(-1) in Guangzhou. In addition, dry and wet deposition fluxes of PAHs were dominated by coarse (D-p > 1.8 mu m) and fine particles (D-p < 1.8 mu m), respectively. Fine particles predominated the deposition of PAHs in the lung. The results estimated by incremental inhalation cancer risk suggested that particle-bound PAHs posed serious threat to human health within the e-waste recycling zone and Guangzhou. (C) 2015 Elsevier Ltd. All rights reserved.